Somatic complications of hyperkinetic syndrome in children - A. A. Lyalina; L. G. Khachatryan (Лечащий Врач, 2021)
The article describes the results of observation of 114 children at the age 1–16 years, with hyperkinetic syndrome as a component of different neurological diseases and their secondary somatic complications. The structure of extrapyramidal disorders in children patients in the sampling was studied, as well as the level of disorders in protein-energetic metabolism, respiratory disorders, secondary orthopedic pathology, visual and hearing impairments, cardiovascular pathology, and intellectual disorders. The analysis results of structure of extrapyramidal disorders were visually presented.